Microbial Troubles of Hospitalization - Parsia, Yasaman; Puteri Fadzline, Muhamad Tamyez; Sorooshian, Shahryar (IJPT, 2017)
The present day’s hospital-acquired infection, also referred to Nosocomial Infection (NI), is not only becoming a major concern for hospitalized patients, but also an expensive burden on a country’s budget. It is discussed in this paper that most of such infections that are reported include urinary tract infection, respiratory tract infection, surgical site infection and blood stream infection. A lot of reports state that NI is a global issue with high mortality rates and it poses a costly challenge for a country’s economy. Even though a lot of prevention strategies are used for controlling NI, it is still a crucial health problem faced by the modern-day world. This letter invites scholars for a better solution suggestion to control of NI.